Register Analysis of A Mild, “How Bold Can You Go”(Systemic Functional Language Approach) - Astrini, Atik; Malika Laila; Dwi Haryanti (Journal of International Multidisciplinary Research, 2024)
Derived from Halliday's systematic functional linguistics, register analysis is useful not only for discourse analysis but also for planning linguistically effective advertising. Register analysis takes into account cultural context, situational context, including field, tenor and form, and human interpretation of text meaning. With this method, assuming that language is an embodiment of a social process, advertising can be designed according to the social reality of the target market. Keywords: register analysis, context of culture, context of situation